NONPOLIO ENTEROVIRUSES WHICH CAUSED THE RISE OF ENTEROVIRUS INFECTION ON SOME TERRITORIES OF RUSSIA IN 2016 - N. I. Romanenkova; M. A. Bichurina; L. N. Golitsyna; N. R. Rozaeva; O. I. Kanaeva; I. V. Cherkasskaya; L. P. Kirillova; A. Yu. Bataeva; A. S. Baryshnikova; N. A. Novikova (Журнал инфектологии)
Aim: Characteristics of the peculiarities and the etiological factor of enterovirus infection on some territories of Russia in 2016. Materials and methods: We investigated 2138 samples from the patients with enterovirus infection. The isolation and identification of enteroviruses were conducted by the virological method and by partial sequencing of the genome region VP1. Phylogenic trees were constructed according to the method of Bayesian Monte Carlo Markov Chain. Results: Epidemic peaks of enterovirus infection were fixed on some territories of Russia. In Saratov region the morbidity index of enterovirus infection in 2016 was twice as high as the median morbidity index over previous years. The morbidity level of enterovirus meningitis – 3, 21 for 100000 of the population (77% from all the cases of enterovirus infection) was higher than on the other territories. In Kostroma region the morbidity index of enterovirus infection in 2016 was 11 times higher than the index of the previous year. On both territories the rise of morbidity depends on the active circulation of enterovirus ЕСНО30. Enteroviruses ECHO30 from Saratov region belonged to two phylogenic groups of genotype h. To one of them belonged viruses ECHO30 from Kostroma region. In Murmansk and Leningrad regions in 2016 most cases of enterovirus infection were represented by hand, foot and mouth disease (HFMD). The grouped foci of infection were registered in some preschool institutions. The etiological factor of this clinical form was Coxsackieviruses A6 belonging to different genetic variants. Conclusion: Epidemic peaks of enterovirus infection with the prevalence of different clinical forms of the disease were provoked by different etiological factors. On territories where enterovirus meningitis prevailed strains of enterovirus ECHO30 belonging to different variants of genotype h were detected. In patients with clinical picture of HFMD from territories where this form was leading the etiological factor of infection was Coxsackievirus A6 of different genetic variants.